MEMBANGUN PENDIDIKAN BAHASA DENGAN KEMBALI PADA PENDIDIKAN PESANTREN DAN ETNOPEDAGOGIK - Moh. Hilmi (JIE (Journal of Islamic Education), 2017)
Developing Indonesian language education requires a strong attitude and discipline that requires education and ethnopedagogic education. The purpose of this paper is to build Indonesian language education to prioritize the values ​​that exist in boarding schools that is the basic capital of religion that makes learners have a strong Islamic foundation or strong faith so that learners do not quickly waver and unstable in determining the direction of life to the fore. While ethnopedagogic education here complement the faith of learners to keep preserving the local culture.